2017
DOI: 10.1302/0301-620x.99b10.bjj-2016-1005.r1
|View full text |Cite
|
Sign up to set email alerts
|

A comparison study of stem taper material loss at similar and mixed metal head-neck taper junctions

Abstract: When taper junction damage is identified during revision of a LD MoM hip, it should be suspected that a male taper composed of a standard CoCr alloy has sustained significant changes to the taper cone geometry which are likely to be more extensive than those affecting a Ti alloy stem. Cite this article: 2017;99-B:1304-12.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 25 publications
1
19
0
Order By: Relevance
“…Since there was no particular hypothesis about the relative level of corrosion at the eight zones, 28 pairwise comparisons were carried out to exhaust the entire pairwise comparison of the zones. The distal region of the medial quadrant was found to have the highest odds of receiving a higher corrosion score which is aligned with the previous findings in the literature that identified the distal region [19,20,27] and the medial quadrant [7,10,16,28] having the highest corrosion scores. Also, this study shows that the distal region of all the four quadrants had more corrosion damage in comparison with the proximal region of those quadrants.…”
Section: Discussionsupporting
confidence: 89%
“…Since there was no particular hypothesis about the relative level of corrosion at the eight zones, 28 pairwise comparisons were carried out to exhaust the entire pairwise comparison of the zones. The distal region of the medial quadrant was found to have the highest odds of receiving a higher corrosion score which is aligned with the previous findings in the literature that identified the distal region [19,20,27] and the medial quadrant [7,10,16,28] having the highest corrosion scores. Also, this study shows that the distal region of all the four quadrants had more corrosion damage in comparison with the proximal region of those quadrants.…”
Section: Discussionsupporting
confidence: 89%
“…Retrieval studies reported material loss from the femoral tapers of CoCrMo femoral heads mounted on titanium alloy trunnions . Similarly, in this hip simulator test, the CoCrMo femoral tapers showed material loss.…”
Section: Discussionmentioning
confidence: 51%
“…43,46,55,56 Retrieval studies reported material loss from the femoral tapers of CoCrMo femoral heads mounted on titanium alloy trunnions. 43,46,47,[57][58][59] Similarly, in this hip simulator test, the CoCrMo femoral tapers showed material loss. A question that may arise is: why did wear arise from the harder CoCrMo alloy femoral taper when the Ti6Al4V alloy trunnion is much softer?…”
Section: Discussionmentioning
confidence: 53%
“…CoCr. [54] Histopathological tissue assessment. This was carried out as has previously been described in greater detail.…”
Section: Blood/serum Metal Ion Testingmentioning
confidence: 99%